Increasing trend of antimicrobial resistance among methicillin-resistant Staphylococcus aureus strains in Southwest Finland, 2007–2016: An analysis of shifting strain dynamics and emerging risk factors - Silvola, Jaakko; Gröndahl-Yli-Hannuksela, Kirsi; Hirvioja, Tiina; Rantakokko-Jalava, Kaisu; Kanerva, Mari; Auranen, Kari; Marttila, Harri; Junnila, Jenna; Vuopio, Jaana (Elsevier BV, 2025)
Objectives: Substantial rise in the annual incidence of methicillin-resistant Staphylococcus aureus (MRSA) was reported in Southwest Finland (12.4 to 24.9/100 000 people) between 2007-2016. To understand the implications of these changes to the management of MRSA, we sought to analyze the antimicrobial resistance (AMR) trends of MRSA in relation with patient characteristics.
Methods: Antimicrobial susceptibility was determined for ten clinically relevant antimicrobials. Strains with resistance to ≥2 antimicrobials were defined multi-resistant. The isolates were spa typed and clustered. AMR trends and risk factors were identified by associating resistant phenotypes with patient demographics.
Results: A total of 983 new MRSA cases were identified between 2007-2016. After 2011, significant increasing trends were observed in the proportion of isolates resistant to clindamycin (13.9 to 31.5%, p<0.001), erythromycin (19.4 to 35.4%, p<0.001) and tetracycline (16.7 to 32%, p<0.001). The proportion of multi-resistant isolates more than doubled from 14.8 to 39.2%. The increasing AMR trend was reflected in the increase of new strain types and the decrease of previously dominant, non-multi-resistant strains. Patient risk factors associated with (p<0.001) the acquisition of multi-resistant strains included community acquisition, livestock contact, hospital care abroad and immigrant status.
Conclusions: Notable increasing AMR trends among MRSA isolates were observed in Southwest Finland, 2007-2016. The shift in patient demographics to younger age groups and community acquisition contributed to the increase in multi-resistant strains. Immigration, contact with hospital environment abroad and contact with livestock were identified as essential risk factors of multi-resistance. The increased level of co-resistance has persisted after 2016.